The Phenomenon of No-Reflow: Physiological Processes and Management - EL Zaky, Manar Mostafa; Roshdy, Hisham Samir; Abdel Kawy, Ahmed Abdelhalim; Maher Allam, Mohammed (Journal of Neonatal Surgery, 2024)
The no-reflow phenomenon is a serious microvascular complication characterized by inadequate myocardial perfusion despite successful restoration of epicardial coronary artery patency, most commonly following percutaneous coronary intervention (PCI) in acute coronary syndromes. This phenomenon is multifactorial in origin, involving microvascular obstruction due to distal embolization, ischemia–reperfusion injury, endothelial dysfunction, inflammation, and microvascular spasm. No-reflow is associated with larger infarct size, impaired left ventricular function, malignant arrhythmias, and increased short- and long-term mortality. Early recognition and prompt management are crucial, as timely pharmacological and mechanical strategies may partially restore microvascular flow and improve clinical outcomes..